2023
DOI: 10.3390/vaccines11010108
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Extracorporeal Membrane Oxygenation (ECMO) for COVID-19 Patients: A Multi-Institutional Analysis

Abstract: Background: In March 2020, COVID-19 was announced as a global pandemic. The first COVID-19 patient was connected to an ECMO device in Israel during that time. Since then, over 200 patients have required ECMO support due to COVID-19 infection. The present study is a multi-institutional analysis of all COVID-19 patients requiring veno-venous (VV) ECMO in Israel. The aim was to characterize and compare the survivors and deceased patients as well as establish risk factors for mortality. Methods: This retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Extensive research has been undertaken to pinpoint the primary risk factors linked to ECMO treatment in patients with COVID-19. Several studies have consistently identified older age as a risk factor for mortality [ 5 , 8 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Extensive research has been undertaken to pinpoint the primary risk factors linked to ECMO treatment in patients with COVID-19. Several studies have consistently identified older age as a risk factor for mortality [ 5 , 8 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute renal failure necessitating CRRT has been identified as a risk factor for mortality in patients with COVID-19 who receive ECMO [ 8 , 17 ]. In line with this finding, our observations revealed a significantly higher rate of CRRT initiation in mortality group than in survival group (94% versus 26.7%, respectively; p<0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Israel, which does not operate specialized ECMO centers, a study reported a mortality rate of 54% among COVID-19 patients who received ECMO. 12 Therefore, we aimed to determine the mortality rates of patients with severe COVID-19 who received ECMO and analyze the associated factors using nationwide data.…”
Section: Introductionmentioning
confidence: 99%